2019
DOI: 10.1136/bcr-2018-229087
|View full text |Cite
|
Sign up to set email alerts
|

Stent graft exclusion of a mycotic profunda femoris artery pseudoaneurysm with 2-year follow-up

Abstract: Mycotic pseudoaneurysms develop at sites of intimal disruption where bacterial invasion occurs. The conventional treatment involves arterial ligation, excision and debridement, followed by a bypass procedure at a later point. Recently, covered stent grafts have been used to treat mycotic arterial aneurysms either as temporary or definitive procedures. However, this is associated with a risk of stent graft infection, recurrence and rupture. There is a paucity of long-term results on the durability of such endov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…13,14 Other causes of PFA PSAs include blunt trauma, infections, hip torsion, and IV drug use. [15][16][17][18] Our study highlighted the rarity of PFA PSAs, with six cases presented to our quaternary center over the past 15 years. Prevalence among men and women were roughly equal, reflecting the current literature.…”
Section: Profunda Femoris Artery Pseudoaneurysmsmentioning
confidence: 73%
“…13,14 Other causes of PFA PSAs include blunt trauma, infections, hip torsion, and IV drug use. [15][16][17][18] Our study highlighted the rarity of PFA PSAs, with six cases presented to our quaternary center over the past 15 years. Prevalence among men and women were roughly equal, reflecting the current literature.…”
Section: Profunda Femoris Artery Pseudoaneurysmsmentioning
confidence: 73%
“…Notably, no reintervention was reported to maintain or restore the patency in these cases, also in those treated for isolate PSA of the profunda femoris artery. 12,[14][15][16][17][18][19][20] The good performance of PFA stent-grafting may be biased by the lack of long-term follow-up on a consistent base: nevertheless, Derom et al 3 reported patency rate at 4 years and similarly, in two cases of our series, we have been able to assess the primary patency rate of the SG at 132 and 144 months. Moreover, the fact that limb salvage was obtained in all patients, it could be a real valuable outcome of interest in these challenging scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…3 In our literature review only five cases were reported involving PFA being of a mycotic origin with only two being in the modern era (which is defined by the era of widespread use of endovascular treatment modalities) (Table 1). [7][8][9][10][11] With the first case being reported on a postmortem examination of a patient who had IE and leg pain in 1890, by Sir Brice Duckworth where a ruptured PFA aneurysm was found. 12 No established guidelines exist on the management of PFA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the cases reported on PFA MAs only a single recent case was managed using an endovascular approach, with all older cases using an open surgical approach. 4,8,9,10,11 Accordingly, few studies have described endovascular approaches either by stenting or embolization for PFA aneurysms as a whole, in both mycotic and non-MAs. In a recent study performed by Khalid et al In 2014 on a successfully repaired non-mycotic ruptured PFA pseudo-aneurysm using a stent graft similar to our approach, they reported in their review that endo-vascular approach using stent graft was performed on other cases of PFA non-MAs with success and can be an alternative to open surgical approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation